On some sea cucumbers (Echinodermata: Holothuroidea) from off the south and west coasts of South Africa collected by the South African Environmental and Observation Network (SAEON) - Thandar, Ahmed S.; Rambaran, Ryan (Zootaxa, 2015)
Twenty four specimens of holothuroids recently received from the South African Environmental and Observation Network (SAEON), collected from off the south and west coasts of South Africa, are herein recorded and/or described. The specimens comprise eight nominal and one indeterminate species and represent both shallow-water and deep-sea forms, distributed from Plettenberg Bay to just north of Lambert’s Bay in the Western Cape Province. There are no new species but two new records for the South African region and extensions of horizontal and bathymetric distributions of the other species. Additions to the South African fauna are Zygothuria lactea (Théel, 1886) and Synallactes cf. challengeri (Théel, 1886). The paper also contains the first definite record of Thyone venusta Selenka, 1868, originally described from the Red Sea. Distribution ranges of the following species have been altered Synallactes viridilimus Cherbonnier, 1952; S. mollis Cherbonnier, 1952 and Psuedostichopus langeae Thandar, 2009.